2021
DOI: 10.1002/anie.202103217
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cyclic Tetrapeptide for Lead Detoxification

Abstract: Lead (Pb) is a ubiquitous poisonous metal, affecting the health of vast populations worldwide. Medications to treat Pb poisoning suffer from various limitations and are often toxic owing to insufficient metal selectivity. Here, we report a cyclic tetrapeptide that selectively binds Pb and eradicates its toxic effect on the cellular level, with superior potency than state‐of‐the‐art drugs. The Pb‐peptide complex is remarkably strong and was characterized experimentally and computationally. Accompanied by the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Remarkably, 2 and 3 outcompete the benchmark drugs against Pb poisoning, ethylenediaminetetraacetic acid and dimercaptosuccinic acid, because these compounds recovered 95 ± 16% and 110 ± 4% of the cells, respectively. 15 Furthermore, the results also reflect a synergistic effect S3. The titration curves were fitted to a oneset-of-sites binding model to all peptides, but 3 was fitted with a two-set-of-sites model using Origin software; UV-monitored back-titrations of peptide−Pb(II) complexes (100 μM) with ZnCl 2 (0.1−1 mM; 1−10 equiv; E) or CaCl 2 (1−10 mM; 10−100 equiv; F).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, 2 and 3 outcompete the benchmark drugs against Pb poisoning, ethylenediaminetetraacetic acid and dimercaptosuccinic acid, because these compounds recovered 95 ± 16% and 110 ± 4% of the cells, respectively. 15 Furthermore, the results also reflect a synergistic effect S3. The titration curves were fitted to a oneset-of-sites binding model to all peptides, but 3 was fitted with a two-set-of-sites model using Origin software; UV-monitored back-titrations of peptide−Pb(II) complexes (100 μM) with ZnCl 2 (0.1−1 mM; 1−10 equiv; E) or CaCl 2 (1−10 mM; 10−100 equiv; F).…”
mentioning
confidence: 99%
“…We recently revealed the potential of de novo cyclic tetrapeptides to detoxify Pb­(II) ions in human cells by tightly and selectively binding them . While initially the metal-binding residues were Cys and Asp, we found that replacing the former with the novel noncanonical amino acid (ncAA) β-mercaptoaspartic acid (β S Asp; X) enhanced the solubility of the leading peptide and its metal affinity, metal selectivity, and detoxification capabilities . These findings are attributed to the chelate effect within this hybrid ligand that binds Pb­(II) ion via the carboxylate and thiolate upon deprotonation, forming a stable five-membered ring.…”
mentioning
confidence: 99%
“…This peptide was found to be superior to the Cys-containing peptide, with improved characteristics in every tested aspect: higher potency in recovering Pb-contaminated cells, lack of toxicity, enhanced affinity, and metal selectivity. [26] It was also found stable toward oxidation and degradation for 48 h in human blood serum, while the Cys-containing peptide underwent oxidation in a similar setup. [26] These results indicate the great promise that ncAAs also hold toward pharmaceutical purposes.…”
Section: Peptide Siderophoresmentioning
confidence: 92%
“…[26] It was also found stable toward oxidation and degradation for 48 h in human blood serum, while the Cys-containing peptide underwent oxidation in a similar setup. [26] These results indicate the great promise that ncAAs also hold toward pharmaceutical purposes.…”
Section: Peptide Siderophoresmentioning
confidence: 92%
See 1 more Smart Citation